LATAR BELAKANG KEMENANGAN PARTAI KONSERVATIF (BORIS JOHNSON) PADA PEMILU INGGRIS TAHUN 2019 - Hudzaifa, Mella; Muharjono, Muharjono (Jurnal Paradigma, 2022)
The victory of the Conservative party (Boris Johnson) in the 2019 British election was very interested case. By considering that the chairman of the Conservative party before, that has resigned from the position of Prime Minister of the UK twice in 2017 and 2019, its surprised fenomena. In addition, the chairman of the party, Boris Johnson, was known as an controversial figure, racist, and rumors of infidelity. But in the 2019 election the Conservative party (Boris Johnson) shown still could managed to get a majority of the vote. For this reason, this journal aims to explored any factors that support the victory of the Conservative party (Boris Johnson) by the theory of voter behavior and with qualitative descriptive methods. As a result, the Conservative party's succeed was motivated by party management and party leaders in responding to and processing issues currently being faced by British society, such as Brexit, health, and crime. In addition, the Conservative party also had loyal voters who come from middle class and also the support of swinged voters. Johnson's success in offering policies on these issues, especially Brexit, has caused working class voters to also choose Conservative party.